Post-Autologous (ASCT) Stem Cell Transplant Therapy in Multiple Myeloma. (24th November 2014) - Al-Mansour, Zeina; Ramanathan, Muthalagu
Abstract : Autologous stem cell transplant (ASCT) is the standard of care in transplant-eligible multiple myeloma patients and is associated with significant improvement in progression-free survival (PFS), complete remission rates (CR), and overall survival (OS). However, majority of patients eventually relapse, with a median PFS of around 36 months. Relapses are harder to treat and prognosis declines with each relapse. Achieving and maintaining "best response" to initial therapy is the ultimate goal of first-line treatment and sustained CR is a powerful surrogate for extended survival especially in high-risk multiple myeloma. ASCT is often followed by consolidation/maintenance phase to deepen and/or maintain the response achieved by induction and ASCT. Novel agents like thalidomide, lenalidomide, and bortezomib have been used as single agents or in combination. Thalidomide use has been associated with a meaningful improvement in PFS and EFS, however, with substantial side effects. Data with lenalidomide maintenance after-ASCT is favorable, but the optimal duration of lenalidomide maintenance is still unclear. Bortezomib use has been associated with superior outcomes, predominantly in high-risk myeloma patients. Combination regimens utilizing a proteasome inhibitor (i.e., bortezomib) with an immunomodulatory drug (thalidomide or lenalidomide) have provided the best outcomes. This review article serves as a review of the best available evidence in post-ASCT approaches in multiple myeloma.